A content analysis of low yat online discussion forums on Malaysian vernacular schools - Daron Benjamin Loo (Penerbit Universiti Sains Malaysia, 2024)
Vernacular schools in Malaysia, while only operating at the primary school level, have had a turbulent existence. Recently, the constitutional legitimacy of these schools was questioned through legal suits brought about by private citizens as well as non-governmental organisations and associations. These suits illuminate the discourses that surround vernacular schools in Malaysia. A discursive space where language use is worth examining is the digital realm, where there is an extent of openness afforded to users to communicate their feelings or views. To this end, three online discussion forums from Low Yat were examined. Posts that had written comments regarding vernacular schools were included. Through qualitative content analysis, six themes were yielded. They revealed perspectives that supported the abolishment of vernacular schools; however, there were also those who presented a contrastive perspective, mainly due to the negative views held against national schools and the educational system. From these posts, stereotypes associated with particular ethnic groups became evident. There were also disagreements towards the purpose and quality of different types of schools. All these indicate how public discourse regarding vernacular schools is complex, as seen through history and compounded by individual social practices.